Cognitive and Evolutionary Inspirations in the Study of Religion with Emphasis on the Development of Ethnology and Sociocultural Anthropology in Slovakia - Michal Uhrin (Svetovi, 2024)
The cognitive and evolutionary approach to the research of religion in cultural and social anthropology has been systematically developing since the 1990s and the first decade of the 21st century. At the end of the 1990s, cognitive and evolutionary theories of religion began to be applied in the research of religion by a narrow group of ethnologists, religionists, and anthropologists in Slovakia. This paper aims to provide a basic overview of the fundamental concepts of cognitive and evolutionary anthropology of religion. It focuses on selected scholars whose works and ideas are considered pivotal in the development of this field. The second objective is to outline how cognitive and evolutionary theories of religion have been reflected in ethnology and sociocultural anthropology in Slovakia.